Graph-based modelling in engineering - Zawislak, Stanislaw; Rysinski, Jacek (Springer, 2016)
This book presents versatile, modern and creative applications of graph theory in mechanical engineering, robotics and computer networks. Topics related to mechanical engineering include e.g. machine and mechanism science, mechatronics, robotics, gearing and transmissions, design theory and production processes. The graphs treated are simple graphs, weighted and mixed graphs, bond graphs, Petri nets, logical trees etc. The authors represent several countries in Europe and America, and their contributions show how different, elegant, useful and fruitful the utilization of graphs in modelling of engineering systems can be.- Resumé vydavatel
Keywords: Graph theory.; teorie grafů; elektronické knihy; electronic books